الوُجُودُ الإلهيُ عِندَ صَدْرِ الدّينِ القُوُنَوِيِ: The Existence of Allah According to Sadr al-Din al-Qaunawi - Abbas Osman, Mohamed Abdelaty (Jurnal Usuluddin, 2024)
This research aims to highlight the position of Imam Sadr al-Din al-Qunawi on the issue of The Existence of Allah as one of the prominent imams of Sufism, who was greatly occupied with research into The Existence of Allah. Because it represents the center around which the circle of their opinions and ideas revolves in general, there are two types of existence for them: pure existence. It is the existence of Allah. And the presence of a viewer ‘Physical Presence’. It is the existence of beings or the world. This is exactly the same position as Imam al-Qunawi. Therefore, the importance of al-Qunawi is due to the fact that he is the true manifestation and pure model of the Sufi position on The Existence of Allah in general.The method used is the inductive and analytical method and the comparative method. The difficulties of the research are that the researcher relied on the sayings of al-Qunawi himself, which are found in his works, which are still ‘manuscripts’ except for rare ones, and reading them is very difficult. The research concluded several results, the most important of which are: al-Qunawi believes that Allah Almighty’s existence is the same as His essence, and His essence is the same as His identity. As for the world, its existence is additional to its essence, but it is a mirror and manifestation of The Existence of Allah. Al-Qunawi divides the levels of the Existence of Allah into two levels (oneness and oneness), and each of the two levels has characteristics and advantages. He also believes that the names and attributes of Allah are legal, and that they are added to Allah Almighty according to considerations determined by effects and circumstances. And that the names of Allah are syncretic and standard, and that His attributes are the same as Himself, which is the same position as the Mu’tazilites. The name (Allah) is a comprehensive, comprehensive, non-restrictive name, and is followed in rank by the name (Lord). In his presentation and presentation of his ideas, he used a mystical and tasteful language, not a verbal or philosophical one.